THEORETICAL DELIMITATIONS IN THE SYNTAX OF THE IMPERATIVE - KELEMEN, Emilia (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Theoretical Delimitations in the Syntax of the Imperative. This present article follows a few theoretical delimitations about the syntax of the imperative based on some theses about the imperative. Firstly, the imperative mood is presented from the traditional grammatical point of view, starting from the GALR, followed by some explanations about the meaning of the imperative enunciation and ersatz imperative. Then, follows a generational approach through a succinct presentation of some theories, which offer new perspectives on imperative, arising a series of questions for which valid answers are still under investigations, for instance, the subject of imperative, the negative imperative, embedded imperatives. We will see if any of these theories apply to the Romanian language, too. Rezumat. Delimitări teoretice în sintaxa imperativului. Articolul de față propune delimitări teoretice privind sintaxa imperativului, pe baza unor lucrări având ca temă (și) imperativul. Mai întâi se prezintă modul imperativ din perspectiva gramaticii tradiționale, pornind de la GALR, după care se fac precizări referitoare la ce înseamnă enunțul imperativ, respectiv imperativele surogate. Apoi, urmează o abordare generativistă, prin prezentarea succintă a unor teorii care oferă perspective noi asupra imperativului, propunând o serie de întrebări la care încă se caută răspunsuri valabile, de exemplu în ceea ce privește subiectul imperativei, imperativa negativă, imperativele încastrate. Rămâne de văzut dacă vreo teorie se aplică și limbii române. Cuvinte cheie: imperativ, subiectul imperativei, imperativ negativ, imperative încastrate.